RANCANG BANGUN PROTOTYPE SYSTEM PENDETEKSI WAJAH DAN PENDETEKSI SUHU TUBUH - Indra Maulana Yusup Kusumah; Khoirida Aelani (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
Face detection is a way of localizing and extracting facial areas that aims for face recognition that is able to identify a person's identity or information from the face. Temperature measurement is a quantity that states the degree of hot or cold an object or object. because a body temperature that reaches 38 Â° C is a sign of disease. The Haar Cascade method has a broad feature set that can be calculated accurately and quickly, it can reduce variability in one class and increase variability between classes, then form a cascade gradually with classification results and detection schemes that are more complex, fast and efficient. This tool uses Arduino Mega as a microcontroller, a webcam as a face detection camera, a MLX90614 sensor as a body temperature detector and a buzzer as a component to provide warnings. In its application, this tool does not require visitors or campus employees and User Control to interact directly. Visitors will follow directions to detect faces, and check temperature, where if it is detected with a high body temperature, the tool will automatically give a warning with a buzzer sound with a long and high tone if the temperature is detected => 37â„ƒ. User Control will receive information on the results of face detection and body temperature from behind the monitor screen.